Effect of geometric factors on performance of a sodium to air heat exchanger in a fast breeder reactor. (January 2015) - Kannan, K.; Vinod, V.; Padmakumar, G.; Rudramoorthy, R.; Rajan, K.K.
Highlights: A heat exchanger analysis (HE) before scale up reduces excess heat transfer area. Representative Elementary Volume analysis of a HE speeds up the solution. The error in air temperature rise prediction by numerical across HE is within 5%. When both pitches are reduced, the maximum increase in heat flux is experienced. The experience has resulted in better design of next level heat exchangers. Abstract: Prototype fast breeder reactor (PFBR) has a safety grade decay heat removal system whose performance depends on the effective functioning of natural convection heat exchangers called sodium to air heat exchangers. The development of Representative Elementary Volume (REV) model for the sodium to air heat exchanger is necessary to envisage its design and to study the effect of various factors for continuous improvement in design. With a Representative Elementary Volume, the hydrodynamic and heat transfer characteristics of the heat exchanger was studied and the results agree well with experimental data. The effect of longitudinal pitch and transverse pitch on the heat exchanger performance has been studied and an improvement of 22% in heat transfer is predicted.